(untitled) (Iranian Journal of Kidney Diseases, 2016)
The information on burden of alcohol abuse in Iran is scarce. However, the available data show that mortality rates and frequency of its use have increased in the Iranian community. In particular, Iran occupies the 1st rank in the number of outbreak incidents and victims of toxic alcohols such as methanol in the Middle East. Mortality and morbidity of toxic alcohols are high if prompt diagnosis and treatment are not initiated rapidly. On-time diagnosis, proper case finding, and standard treatment have an essential role to reduce mortality and morbidity of toxic alcohols particularly blindness and other physical and psychological disabilities. This review focuses on intoxication with methanol, ethylene glycol, and isopropanol, and their treatment.